VD_FINDINFO Arrêt / 2016 / 1029 vom 15. November 2016 - VD Tribunal cantonal (2016)
PRESTATION D'INVALIDITÉ, COMPARAISON DES REVENUS, ACTIVITÉ LUCRATIVE INDÉPENDANTE | 18 al. 1 LAA, 16 LPGA, 4 LPGA, 7 LPGA